Genome-wide identification and expression profiling of MST, SUT and SWEET transporters in Dendrobium catenatum - Weiwei Fan; Huashan Gao; Lei Zhang; Dongdong Mao; Yanyan Li; Lifang Zhang; Jingting Li; Xuyao Zhao; Hongwei Hou (BMC Genomics, 2024)
Abstract Background Sugar transporters (STs) play a critical role in the transportation of sugar, participating in plant growth and development, stress/defense responses, and signal transduction processes. Dendrobium catenatum (also known as Dendrobium officinale, hereinafter referred to as D. catenatum) is an important traditional Chinese medicinal herb with remarkable medicinal properties and possessing high economic value. Polysaccharides are the primary active components in D. catenatum, exhibiting diverse pharmacological activities. Sugar transporters function as material supplier and may play the essential roles in the polysaccharide biosynthesis, as well as the key reulators in the signaling and responses to abiotic stresses in Dendrobium plants. However, a comprehensive analysis of sugar transporters in D. catenatum remains elusive, thereby hindering our understanding of sugar partitioning within this species. Results In this work, the members belonging to MST, SUT, and SWEET gene families were identified in four Dendrobium plants. A comprehensive study of sugar transporters was conducted in D. catenatum, including phylogenetic relationship, structural arrangement, regulatory networks, expression profiles, and potential functions analysis. Seven sugar transporters were found to be involved in the process of polysaccharide biosynthesis in D. catenatum. Red-blue light is an effective way to enhance the accumulation of polysaccharides, and exerts an influence on the expression of polysaccharide biosynthesis related genes. Conclusions This study provide insight into the evolution and functional annotation of sugar transporters in Dendrobium, and establishing a foundation for future functional research of sugar transporters involved in polysaccharide biosynthesis and stress response.